Generation gap in Hatimu Aisyah by Zurinah Hassan: a matter of emotional distance - Mohd Hanafiah, Halis Azhan; Zainon Hamzah, Zaitul Azma (International Journal of Scientific and Technology Research, 2020)
This research aims to discuss ‗generation gap‘ as a matter of emotional distance, as portrayed in the novel Hatimu Aisyah by Zurinah Hassan. The term ‗generation gap‘ is usually associated with the difference in beliefs, thoughts, values and tastes of two different generations, particularly between the old generations and the younger ones. The differences thus cause difficulties in communication, inflict conflicts, and furthermore, may initiate emotional distance between the two generations. The research outlines three objectives to achieve, (1) to identify the characters conflicting with the issues of generation gaps in Hatimu Aisyah by Zurinah Hassan; (2) to classify causes of conflicts pertaining the issues of generation gaps in Hatimu Aisyah by Zurinah Hassan, and (3) to relate the issues of generation gap with social changes in Hatimu Aisyah by Zurinah Hassan. This research employs close reading method. The primary source is the novel Hatimu Aisyah by Zurinah Hassan, first published by Dewan Bahasa dan Pustaka in 1991. The secondary sources include journals, books, articles, references or other sources that enable further understanding on the issues highlighted in the primary source. To clarify further on the issues of generation gaps, the research also employs the theory of Psychosocial Stages of Development by Eric H. Erikson. Erikson outlines eight confronting stages in one‘s life, namely (1) infant (basic trust vs basic mistrust), (2) toddler (autonomy vs shame & doubt), (3) preschooler (initiative vs guilt), (4) school-ager (industry vs inferiority), (5) adolescent (identity vs role confusion), (6) young adult (intimacy vs isolation), (7) middle age (generativity vs stagnation) and (8) older adult (ego-integrity vs despair). The results later indicate that there are four groups of\ people conflicting with the issues of generation gaps, each represented by Aisyah‘s mother (grandmother), Aisyah (mother), Jamilah, Latifah, Hamid, Aziz and Rohani (sons and daughters) and Azizah, Rodiah and Anisah (granddaughters). The causes of conflicts are due to perception of these generations on (1) the types of education they received, (2) the influence of modernization and (3) the decline of traditional customs. It is later clear that the more the younger generations accustomed to the social changes, the wider the gap would be expanded, thus the more possibilities emotional distance occur among the older generations who are still bound to the inheritance.